Employing bioabsorbable grafts in two-stage laryngotracheal reconstruction of pediatric patient with severe subglottic stenosis and history of airway surgery. (December 2018) - Le, Elliot; Tran, Lenhanh
Abstract: A 16-month old female was referred to our practice for laryngotracheal reconstruction (LTR) for acquired subglottic stenosis (SGS) diagnosed at 4 weeks of age due to prolonged intubation. She has a history of open thoracic repair of congenital tracheoesophageal fistula that was complicated by a pneumothorax and phrenic nerve paralysis. We performed a variation of an anterior and posterior cricoid split LTR with tracheal stenting in order to avoid risks of pulmonary morbidity from costochondral cartilage harvesting. We report the first LTR to use KLS Martin Resorb-XG bioabsorbable implant (poly-L-lactic acid & poly glycolic acid) as a substitute graft for autologous cartilage in a patient with severe SGS and a history of airway surgeries. The patient had an uncomplicated recovery and had a patent trachea on laryngobronchoscopy at 4, 13, and 22 months after surgery.